1975
DOI: 10.1002/art.1780180603
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immunoglobulins and complement in rheumatoid articular collagenous tissues

Abstract: Ninety-three patients with a variety of joint diseases were studied for evidence of immune complexes in articular collagenous tissues. Frozen sections of freshly obtained biopsies of hyaline articular cartilage and menisci were stained with fluoresceinated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0
1

Year Published

1975
1975
2009
2009

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 183 publications
(70 citation statements)
references
References 22 publications
(5 reference statements)
2
67
0
1
Order By: Relevance
“…Further studies by us and others revealed that the activated chondrocytes in the superficial layer of cartilage were responsible for much of the NO produced by this tissue (8,9). These findings, coupled to previous studies showing the presence of immune complexes trapped on the surface of rheumatoid cartilage (20), suggested that in this disease, large concentrations of oxygen radicals and NO may coexist at the cartilage surface. Finally, recent studies in our laboratory indicated that H 2 O 2 , and the product of oxidation of NO, nitrite salts, as well as ONOO, were able to cross-link and nitrosate immunocomplexes (10).…”
Section: Discussionmentioning
confidence: 51%
“…Further studies by us and others revealed that the activated chondrocytes in the superficial layer of cartilage were responsible for much of the NO produced by this tissue (8,9). These findings, coupled to previous studies showing the presence of immune complexes trapped on the surface of rheumatoid cartilage (20), suggested that in this disease, large concentrations of oxygen radicals and NO may coexist at the cartilage surface. Finally, recent studies in our laboratory indicated that H 2 O 2 , and the product of oxidation of NO, nitrite salts, as well as ONOO, were able to cross-link and nitrosate immunocomplexes (10).…”
Section: Discussionmentioning
confidence: 51%
“…Numerous aspects of this model have been shown to resemble rheumatoid disease, including in both the immunofluorescent demonstration of immunoglobulins and complement components in ACT surfaces (2,3,15,22). Immuno-em studies of rheumatoid ACT have suggested the presence of IgG and IgM (23).…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes released in the immediate proximity of cartilage are probably of greater importance. They may originate in granulation tissue pannus, or as a consequence of phagocytosis or reversed endocytosis associated with immune complex deposition in the superficial collagenous layer of cartilage (13,14). Such sources of enzymes, however, would only provide a partial explanation for matrix destruction in that proteoglycan depletion may, at times, be observed in midzone and deeper regions of cartilage, which are anatomically divorced from events that occur in the superficial layer (15).…”
Section: Modulation Of Cartilage Destruction By Select Nonsteroidal Amentioning
confidence: 99%